Proposed Service Quality Improvement at Aya Travel using SERVQUAL Method and Importance Performance Analysis - Matthew Ramandri, Andreas; Susanto, Sani; Yusuf W, Yogi (Ann Publisher, 2024)
Intercity travel is a transportation service that facilitates movement between cities and cities. Aya Travel is here to facilitate transportation between Bandung and Depok. Aya Travel was established in 2005 with a fleet of 16 units. As time passes, there are travel competitors whose presence makes the sales of Aya travel departure tickets decline in 2016. This can be caused by the quality of other travel services being better than Aya Travel, so lately, people have switched from Aya Travel. The phenomenon is that what Aya travel consumers expect is not what they receive. Service quality measurement is carried out to respond to the above phenomenon using SERVQUAL. In the process, initial attributes from literature studies and Critical Incident Techniques were collected. After the attributes are collected, the questionnaire is distributed. The Factoring process is carried out to produce factors that are formed so that it is easier for Aya Travel to find out in which dimension it turns out that the quality of the service is inferior. After the SEVQUAL measurement process, an important Performance Analysis process was carried out to find improvement priorities from Aya Travel. The IPA method will map attributes into quadrants to produce priorities ranging from those that must be improved immediately to those that do not add value to the quality of Aya Travel's services. A Factor Analysis was produced from 22 attributes grouped into four factors, and it turned out that the display factor had the worst idea. The measurement of Aya travel service quality produces six attributes that need to be improved, which are those in the second quadrant (Consternate here) in the IPA diagram. For the proposed improvement, a discussion was carried out with Aya Travel so that the improvement proposal could be under the opinions and input of Aya Travel.